The pharmacy study program in Guadalajara: 1839-1919 - García Alcaraz, María Guadalupe; Oropeza Sandoval, Luciano (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: In this article we present an approach to the history of pharmacy education in Guadalajara, a study that covers from 1839, year in which this program was created, until 1919, year in which it was closed at the Escuela Comercial e Industrial para Señoritas. It shows how pharmacy education took shape, its relationship with medicine, the impact of political instability on its evolution, the incidence of pharmacists' work experiences and the emergence of new educational modalities.